Pharmacological Benefits of Porang (Amorphophallus muelleri Blume): A Review - Isnaini, Hanik; Yuhana, Titan Memory; Sholehah, Washeilatus; Jannah, Akyunul (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Porang (Amorphophallus muelleri Blume) is a tuber plant from the Araceae family that grows wild in Indonesian forests. Porang tubers have a high content of the active compound glucomannan, a low-calorie hydrocolloid dietary fiber with various health benefits. However, its potential in the pharmaceutical field has not been fully explored scientifically, so this scientific review aims to explore the potential of glucomannan and other bioactive compounds in porang in the pharmaceutical field based on literature studies, as well as the challenges of developing it as a leading commodity in Indonesia. In addition to glucomannan, porang also contains secondary metabolites such as alkaloid, flavonoids, saponins, tannins, and steroids. Research studies show that porang can be used in the treatment of various diseases, such as diabetes (especially type-2 diabetes mellitus), obesity, hypertension, and has the potential as anti-cholesterol, anti-tumor, anti-inflammatory, prebiotic agent, anti-bacterial, and wound healing. The majority of applications that are still in preclinical in vivo trials on experimental animals and the presence of calcium oxalate as an irritant compound are the challenges of developing Porang as herbal medicine. Therefore, the use of porang as herbal medicine still requires further research regarding safe processing and clinically appropriate dosage. Keywords: cacao fruit-rot, Phytophthora palmivora, biological control, decomposer.